Acid ceramidase regulates innate immune memory - Nils Rother; Cansu Yanginlar; Geoffrey Prévot; Inge Jonkman; Maaike Jacobs; Mandy M.T. van Leent; Julia van Heck; Vasiliki Matzaraki; Anthony Azzun; Judit Morla-Folch; Anna Ranzenigo; William Wang; et al. (Cell Reports, 2023)
Summary: Innate immune memory, also called ''trained immunity,'' is a functional state of myeloid cells enabling enhanced immune responses. This phenomenon is important for host defense, but also plays a role in various immune-mediated conditions. We show that exogenously administered sphingolipids and inhibition of sphingolipid metabolizing enzymes modulate trained immunity. In particular, we reveal that acid ceramidase, an enzyme that converts ceramide to sphingosine, is a potent regulator of trained immunity. We show that acid ceramidase regulates the transcription of histone-modifying enzymes, resulting in profound changes in histone 3 lysine 27 acetylation and histone 3 lysine 4 trimethylation. We confirm our findings by identifying single-nucleotide polymorphisms in the region of ASAH1, the gene encoding acid ceramidase, that are associated with the trained immunity cytokine response. Our findings reveal an immunomodulatory effect of sphingolipids and identify acid ceramidase as a relevant therapeutic target to modulate trained immunity responses in innate immune-driven disorders.